ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN - Hesti Widiastuti; Sri Yuni Widowati (STIE Pelita Nusantara Semarang, 2014)
Purchase decision is a decision for possession of an act of two or more alternative options. Many factors can influence the purchasing decisions of consumers of a product, such as product, price and promotion. Consumer purchasing decisions could be made of many products, one of which is food. This is because basically everyone needs food as supply enough energy to be able to perform daily activities.One of the food it is Mie Jakarta 69. Although it’s been promoted, Mie Jakarta 69 still under another noodle products. The possibility of a marketing strategy that is used through product, price, and promotion is not yet effective, so purchasing decisions against Mie Jakarta 69 still low. The location of this research is the way of MT. Haryono No. 914 B Semarang. While the respondent chosen is consumers who make purchases on the streets of Mie Jakarta 69 of MT. Haryono No. 914 B Semarang. The purpose of this research is to analyze the effect of product, price, and promotion of the purchase decision.Population in this research is consumers who makes a purchase Mie Jakarta 69 which is unknown definite . A sample in this research is partly consumers who makes a purchase Mie jakarta 69 Semarang number 96 respondents . The data in this research is primer and the method use questionnaire. The technique analysis is multiple regression. Results of analysis using SPSS Version 13 shows that:1. The product influential towards purchasing decision significantly2. The price influential towards purchasing decision significantly3. The promotion influential towards purchasing decision significantly4. The product, price and promotion influential towards purchasing decision significantlyThe big influence between product, price and promotion towards purchasing decision is 66,8 % ( Adjusted R Square = 0,668 )